2022
DOI: 10.3389/fmolb.2022.984307
|View full text |Cite
|
Sign up to set email alerts
|

Anti-aging efficacy of solid-state fermented ginseng with Aspergillus cristatus and its active metabolites

Abstract: Aspergillus cristatus is a beneficial fungus of microbial fermented teas such as China’s Fuzhuan brick tea and Pu-erh tea, and is commonly called golden flower fungus (GFF) because its cleistothecium has a yellow millet or sand grain shape. Since natural materials fermented with GFF exhibit various physiological activities, a new active cosmeceutical ingredient was developed by solid-state fermentation of ginseng, a famous active material for healthy skin, with GFF. The extract of solid-state fermented ginseng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In addition, GFFG inhibits TNF-α-induced expression of MMP-1 in skin fibroblasts, an enzyme that breaks down collagen and is a key protein in maintaining skin structure and elasticity. Therefore, through this process, GFFG helps to slow the aging of the skin and prevents the development of wrinkles [92].…”
Section: Fungusmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GFFG inhibits TNF-α-induced expression of MMP-1 in skin fibroblasts, an enzyme that breaks down collagen and is a key protein in maintaining skin structure and elasticity. Therefore, through this process, GFFG helps to slow the aging of the skin and prevents the development of wrinkles [92].…”
Section: Fungusmentioning
confidence: 99%
“…Studies have shown that GFF solid fermented ginseng extract (GFFG) has several advantages including promoting anti-aging effects, enhancing the skin's moisturizing function, promoting the synthesis of hyaluronic acid, enhancing the expression of aquaporin, and increasing the level of filagrat mRNA in skin cells [90]. These activities effectively combat the aging process of the skin by reducing the expression of inflammatory factors, such as TNF-α-induced skin MMP-1 [92].…”
Section: Fungusmentioning
confidence: 99%
“…In addition to polysaccharides, FBT is also rich in small molecule secondary metabolites, mainly including flavane‐3‐alcohols, noisoprene, acylated flavonoid glycosides, and triterpenes. Some compounds show good biological activity (Chen, Li, et al., 2021 ; Kong et al., 2019 ; Lu et al., 2019 ; Park et al., 2022 ; Wang, Du, et al., 2021 ; Zhou et al., 2022 ).…”
Section: Small Molecule Compounds and Their Activitiesmentioning
confidence: 99%
“…Ginseng has been used as a traditional Asian medicine in Korea, Japan, and China for thousands of years (Xiang et al 2008;Liu et al 2021;Li et al 2022). Ginsenosides which are main active constituents of ginseng, have a variety of pharmacological properties such as anti-aging (Park et al 2022), anti-cancer (Hwang et al 2022), anti-diabetic (Park et al 2019), anti-hyperlipidemic (Kwak et al 2010), anti-inflammatory (Cho et al 2023), and anti-obesity activities (Yoon et al 2021).…”
Section: Introductionmentioning
confidence: 99%